2011
DOI: 10.1177/0267658310390503
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic creativity in second language English: wh-scope marking in Japanese-English interlanguage

Abstract: This article documents a fairly rare kind of interlanguage phenomenon, namely one in which interlanguages exhibit syntactic constructions that are grammatical neither in a learner's native language nor in his or her target language, but are nevertheless typologically attested. The target construction is wh-scope marking, a cross-linguistically attested form of complex question formation. Using an elicited production experiment, an off-line acceptability judgment task and an on-line acceptability judgment task,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
22
0
2
Order By: Relevance
“…The English proficiency of the L2 participants were determined by their scores on the Test for English Majors (TEM) Band 4, which classified them as advanced English learners 1 . In order to better understand the individual differences in their English proficiency, a C-test adopted from Schulz (2006) and composed of three short passages with 60 blanks was administered to L2 participants. The average C-test score was 35.05 out of 60 (SD = 6.46).…”
Section: Methodsmentioning
confidence: 99%
“…The English proficiency of the L2 participants were determined by their scores on the Test for English Majors (TEM) Band 4, which classified them as advanced English learners 1 . In order to better understand the individual differences in their English proficiency, a C-test adopted from Schulz (2006) and composed of three short passages with 60 blanks was administered to L2 participants. The average C-test score was 35.05 out of 60 (SD = 6.46).…”
Section: Methodsmentioning
confidence: 99%
“…depending on whether the L1 licenses partial wh-movement or wh-copies (Lutz et al 2000). For instance, German-English learners show different production and comprehension patterns of long-distance wh-movement compared to Japanese-English adults (Schulz 2006(Schulz , 2011Slavkov 2015). Hence, grammatical options in whmovement afforded in the L1 appear to persevere into intermediate and advanced stages of adult L2 learning.…”
Section: L2 Acquisition Of Wh-questionsmentioning
confidence: 99%
“…Support for the ILH can also derive from showing that some set of L2 facts can be explained only by postulating some construct, such as a rule or constraint, that is not motivated for either the NL or TL. Such findings have been reported in various domains over the years, including word-final devoicing (Altenberg & Vago 1983), consonant clusters in onsets and codas (Carlisle 1998), resumptive pronouns in relative clauses (Hyltenstam 1984), verb-second patterns in main clauses (Schwartz & Sprouse 2000), and wh-scope marking (Schulz 2011), among others. In each case the researchers showed that the learner’s IL grammar differed systematically from both the NL and TL.…”
Section: Discussionmentioning
confidence: 63%